UPAYA KEPOLISIAN DAERAH RIAU (POLDA RIAU) DALAM MENGATASI KASUS KEJAHATAN TRANSNASIONAL PEREDARAN NARKOBA DI PROVINSI RIAU STUDI KASUS PEREDARAN NARKOBA DI KABUPATEN BENGKALIS TAHUN 2017-2018 - Putri Eka Lestari; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study describes the efforts of the Riau Regional Police in preventing cases of transnational drug trafficking in the Riau Province, especially in the district of Bengkalis. The geographical condition of Riau Province, which consists of several islands close to the international waterway boundary of the Malacca Strait, has the potentially becoming the target of narcotics smuggling with a relatively short travel time supported by the presence of unofficial ports which are separate from the government supervision, making the island the destination of drug smuggling. This study uses a pluralism perspective, level analysis of nation states, theories of international cooperation, and non-traditional security concepts. Research data is obtained from several sources such as books, journals, official documents, and website as a support. The method used is a qualitative research method. This analysis is based on data obtained from interviews and field surveys that have been written in field notes or official documents. The results of this study indicate that the efforts made by the Riau Regional Police are by collaborating with the Marin Territory Police of the Malaysian Royalty Police (PDRM) Johor Bahru through the implementation of rendezvous which discusses cross-border crime cases that occur along the Malacca Strait international watershed. From the rendezvous implementation, it was agreed that both parties agreed to exchange information, tighten water patrols, and routinely conduct rendezvous every year to overcome transnational crimes that occurred between the two countries. Keyword: Effort, Drug Smuggling, Riau Regional Police, Malaysian Police, Bengkalis District.